Pengaruh Kepercayaan dan Kepuasan terhadap Customer Retention Nasabah PT. Asuransi Bangun Askrida di Kota Padang - Wijaya, Ronni Andri (Jurusan PIPS FKIP UMMY Solok, 2018)
Research objectives to analyze: (1) the influence of trust on customer retention insurance Askrida. And the effect of satisfaction on Askrida's customer retention insurance. The population in this study are customers who already use the services of PT. Asuransi Bangun Askrida (ASKRIDA) Padang for more than 1 year or more. The sampling technique used is purposive sampling. The type of data used in this study are primary and secondary data. Data analysis technique used descriptive and inductive analysis through multiple regression analysis using SPSS program version 22.00. The results of this study indicate that: (1) confidence positively and significantly affect customer customer retention PT. Asuransi Bangun ASKRIDA in Padang city, (2) satisfaction have positive and significant effect to customer retention of PT. Asuransi Bangun ASKRIDA in Padang city.